A COMPARATIVE STUDY OF ASSERTIVE SPEECH ACT TRANSLATION QUALITY IN FAMILY HEALTH TEXTS BY NURSING AND MIDWIFERY STUDENTS - Dessy Dwijayanti; Adianto Budiman, Ramadan (Acceleration: Multidisciplinary Research Journal, 2025)
This study investigates the quality of translations of assertive speech acts produced by nursing and midwifery students. Using a qualitative descriptive approach with a fixed case study design, the research aims to (1) compare translation quality between the two student groups, (2) analyze differences in translation quality, and (3) identify factors influencing these differences. The data consist of 100 assertive speech acts categorized into convincing (37), conveying (44), and stating (19). Five translation techniques were identified: literal translation, transposition, modulation, reduction, and adaptation. The results show that nursing students obtained a higher overall translation quality score (2.78) than midwifery students (2.54), indicating better accuracy, while translations produced by midwifery students demonstrated higher readability. These findings provide practical implications for translation pedagogy, particularly in designing health-related translation instruction that emphasizes both accuracy and readability in academic contexts.